Nutritional immunomodulation of Atlantic salmon response to Renibacterium salmoninarum bacterin - Emam, Mohamed; Eslamloo, Khalil; Caballero-Solares, Albert; Lorenz, Evandro Kleber; Xue, Xi; Umasuthan, Navaneethaiyer; Gnanagobal, Hajarooba; Santander, Javier; Taylor, Richard G; Balder, Rachel; Parrish, Christopher C; Rise, Matthew L (Frontiers in Molecular Biosciences, 2022)
We investigated the immunomodulatory effect of varying levels of dietary ω6/ω3 fatty acids (FA) on Atlantic salmon (Salmo salar) antibacterial response. Two groups were fed either high-18:3ω3 or high-18:2ω6 FA diets for 8 weeks, and a third group was fed for 4 weeks on the high-18:2ω6 diet followed by 4 weeks on the high-18:3ω3 diet and termed “switched-diet”. Following the second 4 weeks of feeding (i.e., at 8 weeks), head kidney tissues from all groups were sampled for FA analysis. Fish were then intraperitoneally injected with either a formalin-killed Renibacterium salmoninarum bacterin (5 × 107 cells mL−1) or phosphate-buffered saline (PBS control), and head kidney tissues for gene expression analysis were sampled at 24 h post-injection. FA analysis showed that the head kidney profile reflected the dietary FA, especially for C18 FAs. The qPCR analyses of twenty-three genes showed that both the high-ω6 and high-ω3 groups had significant bacterin-dependent induction of some transcripts involved in lipid metabolism (ch25ha and lipe), pathogen recognition (clec12b and tlr5), and immune effectors (znrf1 and cish). In contrast, these transcripts did not significantly respond to the bacterin in the “switched-diet” group. Concurrently, biomarkers encoding proteins with putative roles in biotic inflammatory response (tnfrsf6b) and dendritic cell maturation (ccl13) were upregulated, and a chemokine receptor (cxcr1) was downregulated with the bacterin injection regardless of the experimental diets. On the other hand, an inflammatory regulator biomarker, bcl3, was only significantly upregulated in the high-ω3 fed group, and a C-type lectin family member (clec3a) was only significantly downregulated in the switched-diet group with the bacterin injection (compared with diet-matched PBS-injected controls). Transcript fold-change (FC: bacterin/PBS) showed that tlr5 was significantly over 2-fold higher in the high-18:2ω6 diet group compared with other diet groups. FC and FA associations highlighted the role of DGLA (20:3ω6; ...